Case Report: Cerebral Venous Sinus Thrombosis in a Young Child With SARS-CoV-2 Infection: The Italian Experience - Silvestri, Paola; Clemente, Anna; Spalice, Alberto; Febbo, Alessandra; Matera, Luigi; Accardo, Fabiana; Barbieri, Maria Antonietta; Villani, Alberto; Midulla, Fabio (Frontiers in Neurology, 2022)
Introduction: Sars-Cov2 infection in pediatric patients is usually characterized by fever, dry cough and fatigue, or is asymptomatic and rarely presents with pneumonia. On the other side, cerebral venous sinus thrombosis (CVST) could be a neurological sequela of the prothrombotic state triggered by COVID-19 both in adults and children. Case Report: We present a case of a 15-year-old male child, obese and with mild neurocognitive impairment, admitted to the Pediatric Emergency Department and then diagnosed with CVST during Sars-Cov2 infection. Conclusion: During the COVID-19 pandemic, in patients presenting with neurological manifestations of CVST (headache, alteration of consciousness, focal deficit or signs of endocranial hypertension), it is advisable to look for a current or recent infection from SARS-CoV-2, regardless of the presence of respiratory symptoms. In our patient, the ongoing SARS-CoV-2 infection represents the only prothrombotic risk factor underlying the neurological disease.